LANGUAGE, POWER, AND ACCESS: AN ETHNOGRAPHIC STUDY OF LINGUISTIC BARRIERS FACED BY REFUGEES IN HOST COUNTRY HEALTHCARE SYSTEMS - Andi Rahmatia Karim; Yusuf Yusuf; Alaa Chahine (Yayasan Adra Karima Hubbi, 2025)
Global refugee displacement has intensified encounters between linguistically diverse populations and host country healthcare systems, where language frequently operates as a mechanism shaping access, power, and equity. This study aims to examine how linguistic barriers are experienced, produced, and negotiated by refugees within healthcare institutions, with particular attention to everyday interactional practices and institutional language regimes. An ethnographic qualitative design was employed, involving prolonged participant observation, in-depth interviews with refugees and healthcare professionals, and analysis of institutional documents across multiple healthcare sites. Data were analyzed thematically through an iterative process linking micro-level communicative interactions with broader organizational structures. The findings reveal that linguistic barriers are not merely technical communication problems but are structurally embedded in healthcare routines that privilege dominant languages, professional authority, and efficiency. Limited and inconsistent interpreter provision, reliance on ad hoc mediation, and monolingual clinical practices constrained refugees’ participation, informed consent, and continuity of care. Refugees developed adaptive strategies to navigate these constraints, yet such strategies shifted the burden of communication onto patients rather than institutions. The study concludes that language functions as a key mechanism through which healthcare access is regulated and inequality is reproduced. Implications highlight institutional responsibility for equitable, linguistically responsive healthcare systems globally.